Industry 4.0 - Digital Twin Applied to Direct Digital Manufacturing - Vitorino, João (2019)
Marinha Grande is a city in Leiria’s district, Portugal. Marinha Grande is known as the moulding city, influenced by the glass, plastic and rapid manufacturing industry. Its history comes from the 18th century with the first glass factory. In order to improve technological development in the local industry, Centre for rapid and sustainable product development (CDRsp) was established in 2007. With that historical know-how and data-based moulding manufacturing, this work goal is to link that data with today’s technology, implementing the Industry 4.0. That information would be stored in a Cloud-Based Design and Manufacturing (CBDM) as well as the real-time operational data. Accessing to that cloud, the design and production engineers can work together to digitally create a product without having to stop the machinery. To implement these concepts, this paper suggests a Digital Twin (DT) to take advantage of the historical information allied to the existent industrial machinery. It suggests a digital twin of a robotic arm with an additive or hybrid manufacturing tool, printing big parts (e.g. garden benches or urban furniture) with reused materials such as tire, cork, wood or stone pow loads.